Comparison of frequency and magnitude of head impacts experienced by Peewee boys and girls in games of youth ice hockey. Issue 1 (20th May 2021) - Post, Andrew; Karton, Clara; Thevenot, Odette; Hoshizaki, T. Blaine; Robidoux, Michael; Gilchrist, Michael D.
Abstract: In youth ice hockey, girls are reported to suffer more concussions than boys, peaking around 13–14 years old, which may be related to differences in the level of brain trauma experienced by the players. The purpose of this research was to describe the differences in brain trauma characteristics, specifically the magnitude and frequency of head impacts between Peewee boys and girls from playing ice hockey. Thirty games of Peewee boys and Peewee girl's ice hockey were recorded to document the head impact events. These events were reconstructed using physical and computational techniques to estimate the strain to the brain tissue. The results found that Peewee boys experienced more head impacts than girls, specifically from the shoulder, ice, boards, and fist/punches (p < 0.05). The boys also experienced more medium strain category impacts (p < 0.05). These results identify that Peewee boys and girls engage in ice hockey differently, which affects the risk of brain trauma likely to be encountered while during game play, suggesting that the increased rate of concussion for girls may not be related to impact magnitudes within the sport but increased reporting of symptoms of concussion or gender differences in brain tissue response to an impact.